Development and validation of a sepsis diagnostic scoring model for neonates with suspected sepsis - Sokou, Rozeta; Ioakeimidis, Georgios; Piovani, Daniele; Parastatidou, Stavroula; Konstantinidi, Aikaterini; Tsantes, Andreas G.; Lampridou, Maria; Houhoula, Dimitra; Iacovidou, Nicoletta; Kokoris, Styliani; Vaiopoulos, Aristeidis G.; Gialeraki, Argyri; et al. (Frontiers in Pediatrics, 2022)
Background: We aimed to develop and validate a diagnostic model for sepsis among neonates evaluated for suspected sepsis, by incorporating thromboelastometry parameters, maternal/neonatal risk factors, clinical signs/symptoms and laboratory results. Methods: This retrospective cohort study included 291 neonates with presumed sepsis, hospitalized in a NICU, from 07/2014 to 07/2021. Laboratory tests were obtained on disease onset and prior to initiating antibiotic therapy. Τhromboelastometry extrinsically activated (EXTEM) assay was performed simultaneously and Tοllner and nSOFA scores were calculated. Sepsis diagnosis was the outcome variable. A 10-fold cross-validation least absolute shrinkage and selection operator logit regression procedure was applied to derive the final multivariable score. Clinical utility was evaluated by decision curve analysis. Results: Gestational age, CRP, considerable skin discoloration, liver enlargement, neutrophil left shift, and EXTEM A10, were identified as the strongest predictors and included in the Neonatal Sepsis Diagnostic (NeoSeD) model. NeoSeD score demonstrated excellent discrimination capacity for sepsis and septic shock with an AUC: 0.918 (95% CI, 0.884–0.952) and 0.974 (95% CI, 0.958–0.989) respectively, which was significantly higher compared to Töllner and nSOFA scores. Conclusions: The NeoSeD score is simple, accurate, practical, and may contribute to a timely diagnosis of sepsis in neonates with suspected sepsis. External validation in multinational cohorts is necessary before clinical application.